2019
DOI: 10.1097/mot.0000000000000703
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of vascularized composite allograft donation in the United States

Abstract: Purpose of reviewVascularized composite allograft (VCA) donation and transplantation has now demonstrated feasibility and impact to the lives of patients suffering from devastating and traumatic injury. This review summarizes the current landscape of VCA donation in the United States. Recent findingsVCA donations are nonlife-saving allografts, for nonlife-saving transplants -and therefore, conservative donor selection focused on the optimization of donors for the lowest risk to transplant recipients is paramou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…VCA transplantation holds high potential for the recovery of life function and quality for those with catastrophic injury or deformity. [8][9][10][26][27][28][29] This includes thousands of military service members who have suffered traumatic improvised explosive device injuries to the face, neck, limbs, and genitourinary system that, in another era, would have resulted in death for many. 15,30 As a result, the DoD has invested more money and resources in VCA transplantation than any other public or private entity.…”
Section: Discussionmentioning
confidence: 99%
“…VCA transplantation holds high potential for the recovery of life function and quality for those with catastrophic injury or deformity. [8][9][10][26][27][28][29] This includes thousands of military service members who have suffered traumatic improvised explosive device injuries to the face, neck, limbs, and genitourinary system that, in another era, would have resulted in death for many. 15,30 As a result, the DoD has invested more money and resources in VCA transplantation than any other public or private entity.…”
Section: Discussionmentioning
confidence: 99%
“…However, VCA transplantation is a much more novel surgical procedure that may be met with more hesitation in comparison to SOT due to the personal connotation that body parts like the hands, face, or genitourinary organs may carry. 30,35,36 A survey of public opinion regarding willingness to donate one’s face revealed that the main reasons limiting individuals from donating their face included the fear of family members seeing their donated body parts on another individual, fear of losing their identity, and a discomfort surrounding the procurement process and funeral concerns. 37 Despite these hesitations, Plana et al demonstrated that educational initiatives that discuss the indications of FVCA, the process of matching donors with recipients, and operative complications and outcomes may increase the likelihood of individuals’ willingness to donate their face.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited enthusiasm from hand amputees to receive a VCA, despite the increasing number of VCA centres (9). Despite this, 80.3% of those in a government survey were willing to donate their hands and there is evidence that donation is increasing (10). Any discussion is challenging given the limited clinical data available.…”
Section: Donation Screening Matching and Zonal Allocationmentioning
confidence: 99%